People, care and work in the home
1 online resource (xxvii, 279 pages)
Keywords: "Introducing novel theoretical, empirical and practical investigations with case studies from UK, Europe, South America and South East Asia, the book offers a novel global outlook on how contemporary homes are facing genuine challenges from operational, economic, spatial, social and wellbeing perspectives. The changing demographics of our modern society have inevitably impacted the dynamics and relationships within the home from being personal and private to that of multiple work relationships; domestic work, care for older people, or supporting people with special needs. Whilst the home is a concept universally experienced, permeating every aspect of our lives, it remains an entity whose influence on health and wellbeing is poorly understood. This book brings together 17 different contributions from scholars, researchers and practitioners from different disciplinary and professional backgrounds including three feature articles by leading figures, such as Lord Best and Broness Hollins. The chapters are organised within three parts that look at the triangle of people + work + care in the home. At a time when homes are increasingly becoming local hubs for care and wellbeing, this volume is a critical and useful addition to current literature in the social sciences, humanities, economics, culture, care and wellbeing in the domestic sphere"--